Recent outbreak of cutaneous anthrax in Bangladesh: clinico-demographic profile and treatment outcome of cases attended at Rajshahi Medical College Hospital - Siddiqui, Muhammad Afsar; Hossain Khan, Md Azraf; Ahmed, Sk Shamim; Anwar, Kazi Selim; Md Akhtaruzzaman, Shaikh; Salam, Md. Abdus (BioMed Central, 2012)
Background: Human cutaneous anthrax results from skin exposure to B. anthracis, primarily due to occupational exposure. Bangladesh has experienced a number of outbreaks of cutaneous anthrax in recent years. The last episode occurred from April to August, 2011 and created mass havoc due to its dreadful clinical outcome and socio-cultural consequences. We report here the clinico-demographic profile and treatment outcome of 15 cutaneous anthrax cases attended at the Dermatology Outpatient Department of Rajshahi Medical College Hospital, Bangladesh between April and August, 2011 with an aim to create awareness for early case detection and management. Findings: Anthrax was suspected primarily based on cutaneous manifestations of typical non-tender ulcer with black eschar, with or without oedema, and a history of butchering, or dressing/washing of cattle/goat or their meat. Diagnosis was established by demonstration of large gram-positive rods, typically resembling B. anthracis under light microscope where possible and also by ascertaining therapeutic success. The mean age of cases was 21.4 years (ranging from 3 to 46 years), 7 (46.7%) being males and 8 (53.3%) females. The majority of cases were from lower middle socioeconomic status. Types of exposures included butchering (20%), contact with raw meat (46.7%), and live animals (33.3%). Malignant pustule was present in upper extremity, both extremities, face, and trunk at frequencies of 11 (73.3%), 2 (13.3%), 1 (6.7%) and 1 (6.7%) respectively. Eight (53.3%) patients presented with fever, 7 (46.7%) had localized oedema and 5 (33.3%) had regional lymphadenopathy. Anthrax was confirmed in 13 (86.7%) cases by demonstration of gram-positive rods. All cases were cured with 2 months oral ciprofloxacin combined with flucoxacillin for 2 weeks. Conclusions: We present the findings from this series of cases to reinforce the criteria for clinical diagnosis and to urge prompt therapeutic measures to treat cutaneous anthrax successfully to eliminate the unnecessary panic of anthrax.